Diaphyseal Tibia and Fibula Malunion Treated with Open Osteotomy and Internal Fixation: A Case Report - Fauzie, Rivaldy Prayudha Adirachman; Kuswardhana, Helmiyadi (Universitas Islam Negeri Alauddin Makassar, 2024)
Diaphyseal fractures of the tibia and fibula often occur due to traffic accidents. Bone fractures can heal well with proper treatment. However, many cases that are neglected lead to complications such as malunion, particularly in developing countries. Malunion occurs when a fractured bone heals with the fragments in improper positions. Malunion in bone fractures can lead to complications such as decreased bone or limb function, deformities, pain, non-union, avascular necrosis, and limb shortening. This case study reports on a 29-year-old woman with malunion in the tibia and fibula due to a neglected bone fracture for eight months. Symptoms include pain, deformities, and limb shortening. The management involved open osteotomy and ORIF (open reduction with internal fixation), demonstrating that ORIF and osteotomy are successful surgical techniques for correcting malunion in this case. The goals of surgical treatment for malunion are to restore function, reduce discomfort, and correct visually apparent abnormalities.